Caminar como acto y símbolo: análisis del fenómeno devocional y peregrino en torno al Señor del Calvario en Huichapan, Hgo. - Campuzano Cruz, Olivia (Diálogos Latinoamericanos, 2018)
This work presents an analysis of the phenomenon of pilgrimage around the devotion of El Señor del Calvario. It examines its territorial scope in comparison with other pilgrimages in Mexico, the ritual processes in charge of its stewardship, as well as its relations with the devout population. The article finally discusses the social, cultural and political structure that has been built around this practice of popular Catholicism. The methodology consists of a test of hypotheses by documentation, observation as well as interviews and sampling. This project was delimited to analyze our object of study, starting from its contemporaneity in the twenty-first century until the vestiges of its beginnings towards the eighteenth century.